MEMBANGUN KARAKTER PTK-PNF MELALUI PENINGKATAN KOMPETENSI PERSONAL DAN SOSIAL - Harun Al Rasyid (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
Non-formal and informal education is a part of national education that has a broad target. It has large target, geographical variation, and differences in need and demand. To reach this target, this Directorate General is supported by technical and educational staff. The staff are demanded to provide the community with high quality services. They must have personal, social, professional, and academic competences. Although all of these competences have important roles, but this article only discusses personal and social competences. Personal competence gives a strong foundation to deal with all problems, and social competence gives a foundation for human interaction. Both competences influence individual success and reflect the commitment and integrity in their duties.